DIDACTIC WORKS AS AN IMPORTANT PEDAGOGICAL-PSYCHOLOGICAL FACTOR IN FORMING PERFECT QUALITIES IN STUDENTS (Universal International Scientific Journal, 2026)
Didactics is a scientific field aimed at the effective organization of the teaching process and improving the quality of education, the main goal of which is to increase the level of student learning. This thesis examines the theoretical foundations of the creation of didactic principles, their role and significance in the educational process. The created principles are aimed at increasing the effectiveness of teaching, as well as developing independent thinking of students.
Keywords: didactics, social activist, method, moral education, national identity, didactic principles, didactic works, spiritual education, moral development.